The measurement of attitude toward Islam in Pakistan – more positives than negatives?: a response to Hamid et al. (2016). Issue 8 (13th September 2016) - Lewis, Christopher Alan; Musharraf, Sadia
ABSTRACT: It has recently been asserted that the Sahin–Francis Scale of Attitude toward Islam is suitable for use in Islamic contexts. The generalisability of this statement is examined in the light of available evidence from previous studies using the Sahin–Francis Scale of Attitude toward Islam and the Sahin–Francis Scale of Attitude toward Islam Revised. It is proposed that future research within Islamic contexts may wish to employ instruments with no negatively worded items, such as the recently developed Sahin–Francis Scale of Attitude toward Islam Revised.